POLIGAMI PERSPEKTIF FIKIH DAN HUKUM KELUARGA NEGARA MUSLIM - Suud Sarim Karimullah (IAIN Palopo, 2021)
The research of polygamy law focuses on the perspective of fiqh (Islamic Jurisprudence) and family law which is only limited to four Muslim countries, namely Turkey, Tunisia, Indonesia and The Kingdom of Saudi Arabia because the four countries that have been mentioned are countries with a majority Muslim population and become a representation of the four famous jurisprudence school (Madhhabs). Not only that, the family law that exists in these four Muslim countries also has characteristics that are more responsive to all the problems of the family that exist today by being more progressive and giving a new color to Islamic law. Library research is a type of study in this article that collects data through sources of books, journals and various articles that are still relevant to this research with descriptive-qualitative analysis. This article concludes that the provisions of polygamy in fiqh in general have never been prohibited and even there are no sanctions for the perpetrators. This is different from family law regulations in Muslim countries where there are prohibitions and some even provide criminal threats or fines for the practice of polygamy and these regulations are more progressive than the existing legal provisions in fiqh.